2014
DOI: 10.1556/crc.42.2014.3.1
|View full text |Cite
|
Sign up to set email alerts
|

The abiotic stress response and adaptation of triticale — A review

Abstract: After a decade of genetic manipulation and improvement, triticale stand out as a crop of high biomass and grain yield potential which generally surpass that of wheat. Its high productivity is most likely derived from high rates of carbon assimilation linked to stomatal physiology and probably low respiration rate. Being a derivative of rye, triticale has always been assumed to be relatively resistant to abiotic stress. The last review of triticale adaptation to abiotic stress as published by Jessop (1996) poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 82 publications
3
74
0
4
Order By: Relevance
“…Triticale was selected for this study as it out yields wheat in both favourable and unfavourable conditions (Bassu et al, 2011;Estrada-Campuzano et al, 2012). It is also believed that triticale will become more important in the future than wheat if grain quality is improved (Blum, 2014). Its importance will arise due to: climate change; the spreading of agriculture in marginal lands and the need to feed the ever increasing population under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Triticale was selected for this study as it out yields wheat in both favourable and unfavourable conditions (Bassu et al, 2011;Estrada-Campuzano et al, 2012). It is also believed that triticale will become more important in the future than wheat if grain quality is improved (Blum, 2014). Its importance will arise due to: climate change; the spreading of agriculture in marginal lands and the need to feed the ever increasing population under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cooler CT is associated with greater stomatal conductance and increased gas exchange rate under irrigated conditions and better hydration status under drought (Pinto et al 2010). Blum et al (1989) and Blum (2014) found a positive correlation between drought susceptibility and canopy temperature in stressed environments and genotypes with higher yield losses under drought had warmer canopies. In a study on rice, Ahmadikhah and Marufinia (2016) revealed that in severe water deficit, the rice mutant line MT85 (a rice mutant line which was 18 cm shorter than its wild type cv Neda) showed lower loss (19%) in yield as compared to Neda (31%) with high yield loss.…”
Section: Discussionmentioning
confidence: 95%
“…Cereal production per capita in 2012, due to droughts in Australia and the United States amounted to 294 kg and was the smallest in the past 30 years. Blum (2014) emphasizes that one of the solutions is to increase the area under triticale due to the fact that this plant can grow on marginal lands, as well as in arid conditions that are becoming more and more widespread as a result of global climate change. Newer generation of triticale species has significantly improved biological properties and higher quality grains due to increased protein content, especially lysine.…”
Section: The Economic Character Of Triticalementioning
confidence: 99%